2002
DOI: 10.1023/a:1020659227650
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A pot experiment confirmed that pigeonpea could efficiently utilize various sources of phosphorus (P) (aluminium phosphate, iron phosphate and apatite), irrespective of genotype. A qualitative assay method for iron (Fe)-P solubilizing activity showed that root exudates collected from P-deficient pigeonpea contained Fe-P solubilizing substances and that they were released mainly from root tips. Citric, malic, malonic, succinic and piscidic acids were identified in root exudates. Citric and piscidic acids releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…In some studies, increased soil P availability under pigeon pea was attributed to the efficient solubilization and uptake of P from bound sources (e.g. Fe-P) by root exudates (Ae et al 1990;Ishikawa et al 2002) but this aspect was not investigated in the present study.…”
Section: Discussionmentioning
confidence: 79%
“…In some studies, increased soil P availability under pigeon pea was attributed to the efficient solubilization and uptake of P from bound sources (e.g. Fe-P) by root exudates (Ae et al 1990;Ishikawa et al 2002) but this aspect was not investigated in the present study.…”
Section: Discussionmentioning
confidence: 79%
“…JA-Me inducible expression of the promoter of a potato gene for cathepsin D inhibitor in tobacco cell line BY-2 was higher in cells cultured in medium containing BAP than in cells cultured in medium containing 2,4-D, and the repression by 2,4-D was largely released by the addition of aphidicolin an inhibitor of DNA synthesis. These results suggest that JA-Me inducible expression is repressed during active cell divisions (Ishikawa et al 1994b). …”
Section: Gene Expression In Response To Woundingmentioning
confidence: 84%
“…The quantity and type of organic acids by roots highly depended on the plant species, genotypes and growth conditions and so on. According to published literature, under low P stress, the organic acids released into rhizosphere was mainly citrate and malate by white lupin cluster roots [2], piscidic acid by pigeonpea (Cajanus cajan) roots [61], malate and oxalate by soybean roots [62], citrate by Stylosanthes roots [38]. In the study, malate participating in the tricarboxylic acid (TCA) cycle was observed markedly reduced accumulation in stylo roots, as well as its derivative 2-Isopropylmalate.…”
Section: Remodeling Of Organic Acids and Amino Acids Metabolism To Admentioning
confidence: 67%